2016
DOI: 10.1139/cjps-2015-0260
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, physiological, biochemical characteristics and bud success responses of myrobolan 29 c plum rootstock subjected to water stress

Abstract: Water stress treatments on some morphological, biomass, physiological, biochemical characteristics and budding success of apricot and plum cultivars/Myrobolan 29 C plum rootstock have been studied in a pot-experiment trial. Three different water stress levels (control-100 %, medium-75 %, and severe-50 % of the pot capacity) were applied. The results showed that measured morphological, biomass, physiological and biochemical characteristics as well as budding success of cultivars on the rootstocks were affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 33 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, the differences between Garnem and GF 677 were observed. Rootstock influences the scion and increases the plant tolerance against environmental stresses (Bolat et al, 2016;Polat, 2021). In the present study, two peach rootstocks were compared and VXW of GF 677 was found further compared to Garnem.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the differences between Garnem and GF 677 were observed. Rootstock influences the scion and increases the plant tolerance against environmental stresses (Bolat et al, 2016;Polat, 2021). In the present study, two peach rootstocks were compared and VXW of GF 677 was found further compared to Garnem.…”
Section: Resultsmentioning
confidence: 99%
“…The scenario of deficit irrigation is still under research for a few olive cultivars, such as 'Kalamata', which is classified as a drought-sensitive cultivar. Generally, drought mainly impacts plant morphology, physiology, and biochemistry [25]. Under such conditions, xylem vessels become susceptible to embolism or dysfunction, leading to lower hydraulic conductance and carbon intake, which in turn affect plant growth characteristics and productivity [26].…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, several studies have assessed the impact of water shortage on crop yield, especially crop morphology and physiology [7][8][9][10]. However, there have been no investigations into the response of crop production to water shortages [9,11,12].…”
Section: Introductionmentioning
confidence: 99%